2002
DOI: 10.1523/jneurosci.22-01-00193.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient for Both Corticotropin-Releasing Factor Receptor 1 (CRFR1) and CRFR2 Have an Impaired Stress Response and Display Sexually Dichotomous Anxiety-Like Behavior

Abstract: Corticotropin-releasing factor (CRF) and its family of peptides are critical coordinators of homeostasis whose actions are mediated through their receptors, CRF receptor 1 (CRFR1) and CRFR2, found throughout the CNS and periphery. The phenotypes of mice deficient in either CRFR1 or CRFR2 demonstrate the critical role these receptors play. CRFR1-mutant mice have an impaired stress response and display decreased anxiety-like behavior, whereas CRFR2-mutant mice are hypersensitive to stress and display increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
160
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 267 publications
(183 citation statements)
references
References 43 publications
18
160
0
5
Order By: Relevance
“…These data must be interpreted with caution, however, as specific manipulation of Fkbp51 and Crhr2 expression is required to confirm any causal relationship between expression changes and PTSD-like phenotypes observed. Overall, the differential pattern of Crhr2 vs Fkbp51 expression changes in female and male mice supports the hypothesis that sex significantly modulates adaptive responses in CRH signaling during development (Bale et al, 2002;Bangasser et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…These data must be interpreted with caution, however, as specific manipulation of Fkbp51 and Crhr2 expression is required to confirm any causal relationship between expression changes and PTSD-like phenotypes observed. Overall, the differential pattern of Crhr2 vs Fkbp51 expression changes in female and male mice supports the hypothesis that sex significantly modulates adaptive responses in CRH signaling during development (Bale et al, 2002;Bangasser et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…In particular female, but not male, urocortin 2-deficient mice show decreased immobility levels in the forced swim and in the tail suspension tests as well as altered HPA axis activity as compared with wild-type mice (Chen et al, 2006). Moreover, male, but not females, mice born to CRF 2 +/ − or CRF 2 − / − mothers display higher anxiety-like behavior than mice born to wild-type mothers, independently of their CRF 2 genotype (Bale et al, 2002). However, a direct comparison between the latter and the present study is difficult to make.…”
Section: Summary Of the Resultsmentioning
confidence: 89%
“…For example, male mice deficient in both corticotropin releasing hormone (CRH) receptors 1 and 2 exhibit increased anxiety-like behavior in the elevated plus maze, while double mutant females exhibit decreased anxiety-like behavior. 62 Furthermore, human studies have indicated that stressful life events precipitate depressive episodes differentially in women and men. 63 In addition, there is also a sex difference in the heritability of major depression in humans.…”
Section: Discussionmentioning
confidence: 99%